PENGARUH MODAL INVESTASI, MODAL KERJA, TENAGA KERJA, DAN BANTUAN USAHA TERHADAP TOTAL PENERIMAAN UMKM KEK SANUR - Ketut Metria Widiani; Putu Ayu Pramitha Purwanti (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of investment capital, working capital, labor, and business assistance on the total income of micro, small, and medium enterprises (MSMEs) in the Sanur Special Economic Zone (SEZ). This study uses a quantitative approach with a sample of 54 MSME actors and is analyzed using multiple linear regression. The results show that simultaneously all independent variables have a significant effect on total MSME income. Partially, investment capital, working capital, labor, and business assistance have a positive and significant effect on total income. Working capital is the most dominant variable influencing total income. In addition, the study finds differences in the provision of business activity support between MSMEs located in the Natah Antakara area and those outside the area. The conclusion of this study indicates that increasing capital, labor, and business assistance can improve MSME income. Therefore, more equitable policies and support from area managers and local government are needed to enhance the performance of MSMEs.